Spontaneous Stepwise Self‐Assembly of a Polyoxometalate–Organic Hybrid into Catalytically Active One‐Dimensional Anisotropic Structures. Issue 31 (9th July 2014) - Yin, Panchao; Bayaguud, Aruuhan; Cheng, Peng; Haso, Fadi; Hu, Lang; Wang, Joy; Vezenov, Dmitri; Winans, Randall E.; Hao, Jian; Li, Tao; Wei, Yongge; Liu, Tianbo
Abstract An inorganic–organic hybrid surfactant with a hexavanadate cluster as the polar head group was designed and observed to assemble into micelle structures, which further spontaneously coagulate into a 1D anisotropic structure in aqueous solutions. Such a hierarchical self‐assembly process is driven by the cooperation of varied noncovalent interactions, including hydrophobic, electrostatic, and hydrogen‐bonding interactions. The hydrophobic interaction drives the quick formation of the micelle structure; electrostatic interactions involving counterions leads to the further coagulation of the micelles into larger assemblies. This process is similar to the crystallization process, but the specific counterions and the directional hydrogen bonding lead to the 1D growth of the final assemblies. Since most of the hexavanadates are exposed to the surface, the 1D assembly with nanoscale thickness is a highly efficient heterogeneous catalyst for the oxidation of organic sulfides with appreciable recyclability.